Sustainability Analysis and Management Strategy for Sendang Tirta Arum Tourism in Dander District Bojonegoro Regency - Devi Robelina Ardiyanti; Nuddin Harahab; Nurul Badriyah (Postgraduate, University of Mataram, 2025)
Sumberarum Village is one of the villages in Bojonegoro Regency that has developed tourism potential. There are several tourism potentials in Sumberarum Village, namely Sendang Tirta Arum, Guo Lowo and Guo Lawang.However, Sendang Tirta Arum tourism has not been managed well, even though it should be able to have a positive impact on the attractiveness of tourist attractions which ultimately provides welfare for the community. To make this happen, it is necessary to identify the existing ecological, economic, social, and institutional aspects to determine the aspects that require improvement and development. This research aims to find a tourism strategy for Sendang Tirta Arum. The method used is Multidimensional Scaling (MDS) analysis. The resulting index value shows that each dimension analyzed sequentially has a diverse status, namely the ecological, social and institutional dimensions which are very sustainable and the economic dimension which is quite sustainable. The sensitive attributes that most influence sustainability and need to be considered are waste management facilities, business capital assistance, contribution to Original Local Government Revenue, conflicts between government and citizens, the role of private institutions, transportation facilities and infrastructure and the role of environmentally conscious groups.